2019
DOI: 10.4025/revtecnol.v27i1.34002
|View full text |Cite
|
Sign up to set email alerts
|

Farinhas De Banana: Desenvolvimento Do Produto E Sua Caracterização Físico-Química E Funcional

Abstract: Considerando a necessidade de ofertar produtos a partir da banana in natura e o grande interesse da indústria de alimentos pela farinha de banana no estádio de maturação verde, este trabalho teve por objetivo desenvolver e comparar quantitativamente os aspectos físico-químicos e funcionais de quatro farinhas: farinha de banana verde (branqueada ou não) e farinha de banana madura produzida em bancada e comercial. Foram realizadas análises de Aw, cinzas, pH, cor instrumental, proteínas, lipídeos, fibra alimentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
1
0
2
Order By: Relevance
“…The GBF yield in this study was lower than that verified by Polônio et al (2016) -41.07%, but it is close to the indexes determined by Szeremeta et al (2019) and Franca et al (2020) -25.6% and 20.92%. In this way, the GBF yield is quite variable and depends on several factors, including the pulp moisture, plant variety and age, the use of peel, among others (Franca et al, 2020).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The GBF yield in this study was lower than that verified by Polônio et al (2016) -41.07%, but it is close to the indexes determined by Szeremeta et al (2019) and Franca et al (2020) -25.6% and 20.92%. In this way, the GBF yield is quite variable and depends on several factors, including the pulp moisture, plant variety and age, the use of peel, among others (Franca et al, 2020).…”
Section: Resultssupporting
confidence: 70%
“…From this perspective, banana flour stands out as a possible substitute due to its concentration of dietary fiber and pectin (prebiotic agents), phenolic acids (antioxidants that prevent intestinal cancer), high resistant starch content (maintainer of the intestinal epithelium health, especially the colon), minerals (potassium, calcium, magnesium, iron and vitamins A, B1, B2, and C), (Sarawong et al, 2014;Szeremeta et al, 2019), and it has low oil retention capacity in derivatives (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar result to that of the present study was reported by [8] with a yield of around 29.8% when they produced FBV in an industrial tray dryer at 40°C for approximately 24 hours. Lower results were reported by [12] in their study on banana flour: product development and its physicochemical and functional characterization, obtaining a yield of 25.6% for green bananas. On the other hand, [ 1 3 ] reported a higher yield than the present study, 33.9%, in their study on biscuits produced with banana flour: chemical, physical and sensory evaluation.…”
Section: Green Banana Flour Yieldmentioning
confidence: 69%
“…O maior valor médio de pH registrado neste trabalho foi de 6,18 para a farinha de casca de banana no estádio 1 (Tabela 2), sendo que os demais tratamentos (FCB3 e FCB6) não apresentaram diferença significativa. Estes valores obtidos são superiores ao relatado por Szeremeta et al (2019), que analisando as características físico-químicas da farinha da casca de banana verde observaram o valor de 5,69 de pH. De acordo com Carvalho et al (2011), após a colheita à medida que o fruto amadurece, o pH tende a diminuir, comportamento este explicado pela elevação da acidez, que gera um aumento nos níveis de ácidos orgânicos, com predominância do ácido málico, porém podem aumentar no final do amadurecimento ou início da senescência das frutas.…”
Section: Caracterização Das Farinhas De Cascas De Bananasunclassified